APPLICATION OF DNA ANALYSIS APPROACH CONTRIBUTES TO THE IDENTIFICATION OF SEVERAL PLANT SPECIES IN TRUONG SA ARCHIPELAGO, KHANH HOA PROVINCE, VIETNAM - Dinh Duy, Vu; Xuan Dac, le; Dang Hoi, Nguyen; Mai Phuong, Pham; Ngoc Huyen, Dang; Thi Thanh Huong, Tran; Van Thanh, Bui; Tam Thanh, Nguyen; Van Thang, Bui; Thi Phuong, Luu; Thi Thu Hien, Vu; Quoc Khanh, Nguyen (Journal of Forestry Science and Technology, 2021)
DNA barcoding has been widely used to assess species diversity in a variety of ecosystems, including temperate, subtropical, and tropical rain forests. However, due to the difficulties associated with field exploration, most of the species in Truong Sa archipelago have never been barcoded. The purpose of this study is to barcode five species of plants from the Truong Sa archipelago and to provide valuable evolutionary information that will aid in future understanding of the plant community assembly on those particular islands. Using DNA markers (ITS-rDNA), this study created a DNA barcode database for five plant species found on the Truong Sa archipelago. We used the sequence similarity and a phylogenetic based method to the identify 15 samples from five plant species collected in Truong Sa archipelago, Vietnam. Results showed that the PCR success rate for ITS-rDNA region was 100%. The success rate of bidirectional sequencing of PCR product was 100% for 650 bp long the ITS-rDNA region fragment. Phylogenetic analyses using maximum likelihood (ML) indicated that five plant species (PB, BT, BV, NH and TR) had a close relationship with T. argentea, S. taccada, B. asiatica, M. citrifolia, M. citrifolia and C. uvifera, respectively. The current study provided further evidence for ITS-rDNA region as a useful molecular marker for species identification found on other tropical coral islands.